IMPLEMENTASI AJARAN TRI DANA PADA PELAKSANAAN UPACARA YADNYA DI DUSUN BANTAS DESA PAKRAMAN SUDAJI KECAMATAN SAWAN KABUPATEN - Putu Sanjaya (Guna Widya: Jurnal Pendidikan Hindu, 2018)
This paper contains about the implementation of Tri Dana's teachings on the im- plementation of yadnya ceremony in Hamlet Bantas Village Pakraman Sudaji Sawan District Buleleng District. The approach in this paper is descriptive qual- itative, where data is collected through observation and interview. The collected data are then compiled based on the original fact forming a description that cor- responds to the object being observed. Based on the data collected, it can be ar- gued that the teaching of Tri Dana in the implementation of yadnya ceremony has been implemented by krama pakraman Sudaji village. Tri Dana's teachings are implemented in the ceremony of his god Yadnya, Manusa Yadnya, and also Bhuta Yadnya.